(untitled) (Jurnal Intek Akuakultur, 2019)
ARTICLE INFO ABSTRACT Keywords:grouper, rGH, technique,immersion, feed, growth. This study uses the recombinant Growth Hormone (rGH) hormone with different administration techniques (immersion and feed). The purpose of this study was to determine the best technique for giving recombinant Growth Hormone (rGH) to increase growth and survival of Epinephelus fuscoguttatus x E. lanceolatus. The research method used was Completely Randomized Design (CRD) with 3 treatments and 3 K replications without giving rGH; A Through immersion rGH 6 mg / ℓ + NaCL and B Through Feed 6 mg rGH / kg + PBS + Egg Yolk. The best research results with immersion techniques, seen from each parameter starting from absolute weight growth (15.83 ± 2.03g) and survival (97.78 ± 3.85%) Gedung FIKP Lt.II Jl. Politeknik Senggarang, 29115, Tanjungpinang,Telp: (0771-8041766, Fax. 0771-7004642. Email: riduaniwan1995@gmail.com, wiwinbungo@yahoo.com, triyuliantobdp@gmail.com.